Murrinh niyith-niyith peningingtha Adam i Eve = The story of Adam and Eve. - Wycliffe Bible Translators ([Darwin] : Wycliffe Bible Translators, 1989)
Bible story of Adam and Eve.
Text in Murrinhpatha and English.
Keywords: Murrinhpatha language -- Readers; Religions - Christianity - Bible translations; Murrinhpatha language (N3) (NT SD52-11); Education - Language - Indigenous languages; Murrinhpatha -- Murrinh-patha language (N3) (NT SD52-11); Arnhem Land (NT)